Distance learning at the university level / Anis Zafirah Azmi and Mohd Asyraf Md Surani - Azmi, Anis Zafirah; Md Surani, Mohd Asyraf (Universiti Teknologi MARA, Perak, 2019)
Nowadays, as well as fast development in Information Technology and new improvements in learning technology has been rapidly widespread across the globe. Application of distance learning among university are popular in this modern era because it easier the student and the lecturer to interact without attend the real class but still having a class online with the real time in the virtual world. This paper describes on distance learning at the university level which is supported through advanced technology that has evolution from the past decade because of the universal presence of the Internet and also describe the impact for the university student on distance learning.